2014
DOI: 10.1007/s10853-014-8463-1
|View full text |Cite
|
Sign up to set email alerts
|

Fully coupled thermal–electric-sintering simulation of electric field assisted sintering of net-shape compacts

Abstract: A fully coupled thermal-electric-sintering finite element model was developed and implemented to predict heterogeneous densification in net-shape compacts using electric field assisted sintering techniques (FAST). FAST is a single-step processing operation for producing bulk materials from powders, in which the powder is heated by the application of electric current under pressure. Previous modeling efforts on FAST have mostly considered the thermal-electric aspect of the problem and have largely neglected the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The potential of SPS for near-net-shaping has been recognized and some studies have reported the formation of complex-shaped samples, with more or less pronounced deviations from the cylindrical symmetry, for materials as diverse as porous silica monoliths [3], oxide composites [4], silicon carbide [5], coatings on Ni-based superalloys [6], and TiAl alloys [7]. However, so far there are only a few studies addressing the problem theoretically [8][9][10], investigating the impact of the sample geometry, size and heterogeneous stress states on the non-uniformity of temperature, relative density, and grain size spatial distributions. The aim of this paper is to investigate the direct preparation by SPS of copper samples with the so-called dog-bone shape used for tensile tests specimens.…”
Section: Introductionmentioning
confidence: 99%
“…The potential of SPS for near-net-shaping has been recognized and some studies have reported the formation of complex-shaped samples, with more or less pronounced deviations from the cylindrical symmetry, for materials as diverse as porous silica monoliths [3], oxide composites [4], silicon carbide [5], coatings on Ni-based superalloys [6], and TiAl alloys [7]. However, so far there are only a few studies addressing the problem theoretically [8][9][10], investigating the impact of the sample geometry, size and heterogeneous stress states on the non-uniformity of temperature, relative density, and grain size spatial distributions. The aim of this paper is to investigate the direct preparation by SPS of copper samples with the so-called dog-bone shape used for tensile tests specimens.…”
Section: Introductionmentioning
confidence: 99%
“…The SPS process can be applied to metallic as well as to ceramic powder compacts; however, the manner the current flows through the powder-die assembly strongly depends on the electric conductivities of the powder and the surrounding die. Previous thermal-electrical model simulations have shown that for insulating powders almost all the current flew through the conductive graphite die [1][2][3][4]. In the case of oxides, only a small current portion is believed to flow through the dielectric powders.…”
Section: Introductionmentioning
confidence: 99%